2022
DOI: 10.1177/10946705221110845
|View full text |Cite
|
Sign up to set email alerts
|

Using Information-Seeking Argument Mining to Improve Service

Abstract: If service providers can identify reasons users are in favor of or against a service, they have insightful information that can help them understand user behavior and what they need to do to change such behavior. This article argues that the novel text-mining technique referred to as information-seeking argument mining (IS-AM) can identify these reasons. The empirical study applies IS-AM to news articles and reviews about electric scooter-sharing systems (i.e., a service enabling the short-term rentals of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…(2019) also found that the existing service literature disproportionally focuses attention on the managerial consequences of new service technologies (e.g. Skiera et al. , 2022) rather than on the impact of these technologies on consumers (e.g.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) also found that the existing service literature disproportionally focuses attention on the managerial consequences of new service technologies (e.g. Skiera et al. , 2022) rather than on the impact of these technologies on consumers (e.g.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Kunz et al (2019) also found that the existing service literature disproportionally focuses attention on the managerial consequences of new service technologies (e.g. Skiera et al, 2022) rather than on the impact of these technologies on consumers (e.g. Kipnis et al, 2022;Pantano and Scarpi, 2022), though studies of both outcomes are certainly represented.…”
Section: Conceptual Background 21 Artificial Intelligence (Ai) In Ser...mentioning
confidence: 99%
“…Belk’s article on love and sex doll as service workers addresses how AI can provide artificial emotional comfort for customers at the micro-level, Skiera et al’s information-seeking argument mining provides a high-tech approach to improving the provision of preferred service at the meso-level, and Mishra and Makridis’ article on AI service and well-being provides macro evidence for how AI drives economic growth and well-being.…”
Section: Ai Service and Emotionmentioning
confidence: 99%
“…However, the current WOM knowledge is limited to traditional two-dimensional platforms (e.g. Trust Pilot) or social media websites (Filieri et al , 2018a; Filieri, 2016; Mladenović et al , 2020; Skiera et al , 2022) and does not reflect the immersive nature of Metaverse-like environments. Given the depth and breadth of the environment, the behavior will hypothetically change (Belk et al , 2022), and the domain knowledge, although rapidly evolving, is still scattered and inconclusive.…”
Section: Introductionmentioning
confidence: 99%